VD_FINDINFO MP / 2022 / 4 vom 17. August 2022 - VD Tribunal cantonal (2022)
POSITION DOMINANTE, USAGE ABUSIF, RESTRICTION À LA CONCURRENCE, MONOPOLE ÉCONOMIQUE | 28 al. 2 CC, 28 CC, 28a CC, 4 al. 2 LCart, 7 LCart, 137 al. 1 LDIP, 90 CPC (CH)